Effect of Street Trade among School-Going Girls in Kenema City, Sierra Leone (American Journal of Arts and Human Science, 2023)
The prevalence of street trading both at the national and international level has become a global concern and thus undermined economic development. School-going girls in Sierra Leone are the most vulnerable and their involvement in street trading cannot be over-emphasized. Street trading is the selling of goods or food items along the road, footway, or area without legal authority and it is normally associated with parents sending children of school age to trade as a way of boosting family income. This study investigates the effects of street trading on girls-child education in Kenema City. Similarly, challenges associated with street trading, its impact on girls-child education, and possible recommendations for curbing street trading were pinpointed. Sixty (60) respondents were interviewed in all, 50 school-going girls within the age bracket of 5-18 years and 10 parents (26 years and above). The findings of the study will be useful to the Government of Sierra Leone, Non-governmental organizations, policy-making institutions, and the general public. This study will also provide an insight on the causes of the street trade by school-going girls and suggest recommendations to curb this activity in Kenema city, Sierra Leone.